On user perception of safety in online social networks. (1st January 2013) - Lorentzen, Charlott; Fiedler, Markus; Johnson, Henric
Today, many people share personal information through online social networks, and thus they are exposed to the risk to get their accounts compromised, with consequences for their professional and private lives. It is observed that users tend to shortcut labourious security measures, which alleges that their perception of their safety on the social network deviates from the real situation. We investigate how users of social networks perceive safety and how they contribute to it. First, we examine the question how user perception of safety is affected negatively by increased login response times. To this end, we studied teenage users of the online social network Facebook. Second, in order to find out to which extent users are aware of the risks associated with weak passwords, a survey about password complexity in online social networks was conducted. Indeed, we observe differences in password complexity between teenagers with different levels of technical education.